Widespread exposure to Crimean-Congo haemorrhagic fever in Uganda might be driven by transmission from Rhipicephalus ticks: Evidence from cross-sectional and modelling studies. Issue 6 (December 2022) - Lule, Swaib A.; Gibb, Rory; Kizito, Dennison; Nakanjako, Gladys; Mutyaba, Joseph; Balinandi, Stephen; Owen, Leah; Jones, Kate E.; Abubakar, Ibrahim; Lutwama, Julius J.; Field, Nigel
Highlights: Crimean-Congo haemorrhagic fever (CCHF) is a major public health concern throughout Africa. We did a cross-sectional study at three urban abattoirs receiving cattle from across Uganda. CCHF virus seropositivity was high in humans (10.3%) and cattle (69.7%), and viral antigen was present in ticks (mainly Rhipicephalus appendiculatus ). Ecological modelling predicted high human CCHF risk across much of Uganda. Predicted environmental suitability was low for Hyalomma, but high for Rhipicephalus and Amblyomma ticks. Summary: Background: Crimean-Congo haemorrhagic fever (CCHF) is a widespread tick-borne viral infection, present across Africa and Eurasia, which might pose a cryptic public health problem in Uganda. We aimed to understand the magnitude and distribution of CCHF risk in humans, livestock and ticks across Uganda by synthesising epidemiological (cross-sectional) and ecological (modelling) studies. Methods: We conducted a cross-sectional study at three urban abattoirs receiving cattle from across Uganda. We sampled humans ( n = 478), livestock ( n = 419) and ticks ( n = 1065) and used commercially-available kits to detect human and livestock CCHF virus (CCHFV) antibodies and antigen in tick pools. We developed boosted regression tree models to evaluate the correlates and geographical distribution of expected tick and wildlife hosts, and of human CCHF exposures, drawing on continent-wide data. Findings: The cross-sectional study found CCHFV IgG/IgM seroprevalence in humans of 10·3% (7·8–13·3), with antibody detection positively associated with reported history of tick bite (age-adjusted odds ratio = 2·09 (1·09–3·98)). Cattle had a seroprevalence of 69·7% (65·1–73·4). Only one Hyalomma tick (CCHFV-negative) was found. However, CCHFV antigen was detected in Rhipicephalus (5·9% of 304 pools) and Amblyomma (2·9% of 34 pools) species. Modelling predicted high human CCHF risk across much of Uganda, low environmental suitability for Hyalomma, and high suitability for Rhipicephalus and Amblyomma . Interpretation: Our epidemiological and ecological studies provide complementary evidence that CCHF exposure risk is widespread across Uganda. We challenge the idea that Hyalomma ticks are consistently the principal reservoir and vector for CCHFV, and postulate that Rhipicephalus might be important for CCHFV transmission in Uganda, due to high frequency of infected ticks and predicted environmental suitability. Funding: UCL Global Challenges Research Fund (GCRF) and Pan-African Network on Emerging and Re -Emerging Infections (PANDORA-ID-NET) funded by the European and Developing Countries Clinical Trials Partnership (EDCTP) under the EU Horizon 2020 Framework Programme for Research and Innovation.